Jean Jacques Rousseau i Jędrzej Śniadecki o fizycznym wychowaniu dzieci - Nitecka Walerych, Anna (Biuletyn Historii Wychowania, 2016)
In this paper I focus on a comparison of two works: “Emile, or On Education” (1762) by the Geneva philosopher, J. J. Rousseau, and “O fizycznym wychowaniu dzieci” [Eng. On the Physical Upbringing of Children] (1805) by a Polish scholar, J. Śniadecki, in particular on those fragments that relate to the physical (corporeal) raising of children. Both the authors were renowned figures from the age of Enlightenment, they both subjected the then methods of raising children to criticism, and postulated changes contained in their reform programmes. They both proposed specific guidelines, theoretical and practical advice, and also recommendations on pupils’ health and physical upbringing. What is essential in the paper is the widely understood contexts of the two works being created. I took into consideration both the specific social-and-cultural conditions and the climate of the epoch, the level of health education, hygiene practices, as well as Rousseau’s and Śniadecki’s personal experience. The two authors had seminal views on many issues, for instance, they agreed on the issue of nursing treatments of toddlers and care for children, yet there were also significant differences in their beliefs. The cardinal difference concerned the approach to disabled and handicapped children. The works being discussed are strongly embedded in the realities of life in the eighteenth century, and they have exerted a significant impact on the development of contemporary pedagogical thought.